Supeltas dalam Tinjauan Asas Kepastian Hukum - Adityo, Rayno Dwi (Universitas Serang Raya, 2024)
Volunteer traffic controllers (Supeltas) continue to increment along with the increase in traffic flow. Their existence has a two-sided assessment, some welcoming their presence and others rejecting it. Departing from the opinion or information that supeltas have an explication legal basis in the traffic and transportation regulation, the researcher tries to analyze deeper. How is the legal framework of supeltas and how is the position of supeltas in terms of the principle of legal certainty. The purpose of this research is first, to see and describe the position of supeltas in terms of the principle of legal certainty. Second, as material for further research that focuses on the issue of traffic order in legal science perspective. This research uses descriptive analytical with normative juridical research, with a research approach used statue approach and library approach. The kind of data used is secondary consisting of primary legal materials such as regulations and undang-undang, secondary legal materials law like books, scientific journals of law, other scientific journals and tertiary materials such as websites, electronic mass media news, legal and general encyclopedias, language dictionaries. The results showed that the rules of supeltas has not fulfilled the principles of legal certainty and defined authority and has not fulfilled the elements of legal protection for all parties including the traffic control volunteers themselves.